The `inverse relationship` between social capital and sport: a qualitative exploration of the influence of social networks on the development of athletes - Rosso, E. G. F. (Asia Pacific Journal of Health, Sport and Physical Education, 2016)
Sport players' likelihood to fulfil their career expectations is influenced by both technical and non-technical aspects, including self-drive, self-confidence and access to high-quality coaching and to positive learning environments. Among other factors, belonging in the `right` social networks may help players to gain access to critical resources that can ultimately have a significant impact on their career prospects. This includes social capital. Drawing on an empirical qualitative study of women's soccer in South Australia, this paper seeks to provide a broader conceptual and methodological framework to further investigate the `inverse relationship` between sport and social capital, that is, social capital as a component of sport and athlete development. In particular, this paper makes the case for a qualitative approach to explore the influence of social networks and social capital on the career of athletes. The paper draws on primary data from interviews and surveys with players, coaches, administrators and parents and argues that social capital is an important matter to consider when looking at athlete development. Importantly, the paper recognises that social capital may also have negative consequences for the advancement of athletes' careers.